Peran Artificial Intelligence Dalam Meningkatkan Inovasi Metode Dan Media Pembelajaran IPS Oleh Guru Di UPT SPF SD Inpres Perumnas IV Tamalate Makassar - Herdian Erlangga; Irfat Mahmud; Ahmad Syawaluddin; Hasni (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The development of digital technology has brought significant changes in the field of education, including in the learning process at elementary schools. One of the technologies that has begun to be utilized in learning activities is Artificial Intelligence (AI). This study aims to analyze the role of Artificial Intelligence in enhancing the innovation of teaching methods and learning media for social studies by teachers at UPT SPF SD Inpres Perumnas IV Tamalate Makassar. This research uses a qualitative approach with data collection techniques through interviews with three teachers. The results of the study show that the use of AI helps teachers in preparing learning materials, creating practice questions, designing more creative teaching methods, as well as developing more engaging and interactive learning media. The use of AI also increases student activity and interest in learning social studies.However, there are several obstacles in the utilization of AI, such as limitations in internet connectivity, teachers' ability to use technology, and the potential dependence of students on AI. Therefore, it is necessary to improve teachers' digital literacy as well as provide adequate technological facilities so that the use of AI in learning can run optimally.